EFEKTIFITAS PENERAPAN PIDANA MATI DALAM PERSPEKTIF TINDAK PIDANA KORUPSI DI INDONESIA - Prayudi Saputra, Rian (Pahlawan Tuanku Tambusai University, 2022)
The death penalty in Indonesia has basically been introduced and listed in the Criminal Code, which is contained in the first book of Rules Chapter II Article 10 concerning crimes. The death penalty is basically a classic form of punishment, which is assumed to be a form of punishment capable of deterring perpetrators who commit crimes. There is only 1 (one) article regulating the death penalty in the Corruption Crime Law, namely Article 2 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption Crimes. In the elucidation of Article 2, what is meant by